Topical Ophthalmic Cyclosporine in the Treatment of Toxic Epidermal Necrolysis - Zafer Onaran; Gülşah Usta; Mukadder Koçak; Kemal Örnek; Ünase Büyükkoçak (Case Reports in Medicine)
Aim. To describe a case of toxic epidermal necrolysis (TEN) with ocular involvement treated with topical ophthalmic cyclosporine. Case Presentation. A 20-year-old woman developed TEN following administration of carbamazepine that was prescribed for epilepsy. Ophthalmic examination revealed bilateral pseudomembranous conjunctivitis. She was hospitalized in the intensive care unit and treated with intravenous corticosteroid and immunoglobulin. Topical cyclosporine was used in combination with topical corticosteroids for ocular surface disease. Following two months of ocular treatment, she recovered without any severe ocular complication. Ocular examination at the four-month followup showed a 2 mm of symblepharon in the lower fornix as the sole pathologic finding. Conclusion. Topical ophthalmic cyclosporine may contribute to decrease the ophthalmic complications of TEN and should be considered in the acute stage of the disease.